Asserting Accountability to Address Diversity: Report Card as a System of Measurement (Mary Ann Liebert, 2023)
Problem: To the best of our knowledge, there are no standard accountability measures for diversity efforts at the departmental level. Therefore, the purpose of this study is to evaluate a multiprong report card as a structure for evaluation, tracking, and reporting as well as to examine any relationships between expenditures and outcomes. Approach: We instituted an intervention that offered leadership a report card of metrics related to diversity efforts. Included are diversity expenditures, benchmark demographic and departmental data, applications to support faculty salaries, participation in clerkship programs focused on attracting diverse candidates, and requests for candidate lists. The purpose of this analysis is to demonstrate the impact of the intervention. Outcomes: A significant relationship was found between faculty funding applications and under-represented minority (URM) representation in a department (0.19; confidence interval [95% CI] 0.17?0.21; p<0.001). An association was also found between total expenditures and URM representation in a department (0.002; 95% CI 0.002?0.003; p<0.001). Other outcomes include the following: (1) women, URM, and minority faculty have all increased in representation since tracking began; (2) diversity expenditures and faculty opportunity fund and presidential professorship applications have increased over time; and (3) a steady decline in departments with zero URM representation after the tracking of diversity expenditures in both clinical and basic science departments. Next Steps: Our findings suggest that standardized metrics for inclusion and diversity initiatives promote accountability and buy-in from executive leadership. Departmental detail enables tracking of progress longitudinally. Future work will continue to evaluate the downstream effects of diversity expenditures.